The tooth factor effect on the harmonics of large electrical machines - Ayman Y. Al-Rawashdeh; Ali Dalabeeh; Abdallah Al-Zeyod; Ashraf Samarah; Ghazi Qaryouti; Omar Albarbarawi (Bulletin of Electrical Engineering and Informatics, 2020)
In the current study, the general mathematical model for the calculation and analysis of asynchronous systems and transient cases in asynchronous synchronous large electrical machines was developed. The theory of magnetic fields in the teeth's circuits with a smooth surface of the rotor was used and at the same time, high harmonics of magnetic fields and its effect on the transient cases was also calculated. Performance curves were investigated using Matlab codes and evaluated under different values of  factor. The results confirmed the possibility of improving the noise harmonics on the sinusoidal wave form, which is reflected on the machines starting.